Pentecostalism and Indigenous Culture in Northern North America - Westman, Clinton N. (Anthropologica, 2013)
Pentecostalism is a major movement among North American Indigenous people, yet, until recently, anthropolo gists largely ignored it. Mainly since 2001, a small body of literature, focusing largely on Northern North America, has addressed this phenomenon, largely with the intent of either showing that Pentecostal is irrevocably against the Indigenous culture, or, conversely, embedded within it. I present and sum marize primary field data from northern Alberta, while also synthesizing theoretical and empirical contributions from other scholars working on Pentecostalism in Indigenous communities. I critique and problematize particularly the suggestion of Kirk Dombrowski (2001) that Pentecostalism is largely "against" In digenous culture.